The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/iae.0b013e318232c37c
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of a Taurine-Containing Irrigation Solution for Vitrectomy

Abstract: A taurine-containing irrigation solution may protect retinal ganglion cells against excitotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Consistent with many previous studies, taurine exerted a benificial effect on the viability and proliferation of NSCs [22][23][24][25][26]. Our results clearly demonstrated that taurine treatment (5-20 mM) significantly promoted cell viability by MTT assay (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with many previous studies, taurine exerted a benificial effect on the viability and proliferation of NSCs [22][23][24][25][26]. Our results clearly demonstrated that taurine treatment (5-20 mM) significantly promoted cell viability by MTT assay (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…2). Of note, NSCs grew normally in culture without taurine, and it was reported that taurine treatment during the first 1.5 h in culture was not sufficient to sustain its effect on increasing BrdU incorporation [12,25,27,28]. This observation suggests that the action of taurine requires a prolonged incubation with cells therefore is not the result of shortterm effects, such as membrane stabilization or activation of membrane-located proliferation receptors [12,29].…”
Section: Discussionmentioning
confidence: 82%
“…The high glutamate concentration is necessary, because we used the RGC-5 cell line and not primary RGCs. 15 RGC-5 cells are much more insensitive than primary RGCs, and therefore the concentrations of different drugs found (like in our study 9 mg/mL CSA) cannot be translated to primary cells or in-vivo situations. Therefore, also no conclusions about a possible immunosuppressant or toxic effect of CSA for the found CSA concentration in an in-vivo situation can be drawn.…”
Section: Discussionmentioning
confidence: 75%
“…15,36 However, a comparison between the results has to be interpreted with caution, because the experimental settings were different in each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation